2000
DOI: 10.1046/j.1365-2036.2000.014s1109.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric acid secretion in dogs in response to combinations of beer, ethanol and peptone meal – the role of endogenous gastrin

Abstract: Aim: To examine the effects of beer, ethanol, peptone meal and combinations of either peptone meal and beer or peptone meal and ethanol on gastric acid secretion in vagally denervated pouch dogs. Methods and Results: The oral administration of either 200 mL of beer, 5% ethanol or 10% peptone meal signi®cantly stimulated gastric acid secretion for 60± 90 min in these dogs. With 5% ethanol the plasma gastrin concentration was not affected for 90 min. Combinations of 10% peptone and beer (peptone±beer) or 10% pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
(27 reference statements)
0
5
1
Order By: Relevance
“…Indeed, we have already reported that S‐0509 significantly inhibits gastric acid secretion induced by beer in Heidenhain pouch dogs 11 , . 12 Nonetheless, in the present study, S‐0509 as well as atropine had little or no effect on wine‐stimulated acid secretion in IBMX‐pretreated glands. It is of interest that only famotidine significantly inhibited the wine‐stimulated gastric acid secretion.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Indeed, we have already reported that S‐0509 significantly inhibits gastric acid secretion induced by beer in Heidenhain pouch dogs 11 , . 12 Nonetheless, in the present study, S‐0509 as well as atropine had little or no effect on wine‐stimulated acid secretion in IBMX‐pretreated glands. It is of interest that only famotidine significantly inhibited the wine‐stimulated gastric acid secretion.…”
Section: Discussioncontrasting
confidence: 68%
“…[7][8][9][10] It has been found that circulating gastrin levels are regularly increased after beer or wine administration and that a selective CCK-2 receptor antagonist inhibits beer-stimulated acid secretion in a dose-dependent manner in dogs. 11,12 Accordingly, an increase in gastrin level has been postulated to be the main driving force behind increased acid secretion. Against this, however, several compounds, including maleic acid and succinic acid, in fermented alcoholic beverages, have been found to stimulate gastric acid secretion without increasing gastrin levels.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that, in addition to the direct protein effect, the EHC may contain bioactive peptides which may have specific effects in modifying the secretion of components of endogenous protein, including digestive enzymes and mucin. Partial hydrolysates of proteins have been shown to be potent stimulants of gastric acid and pancreatic secretions ( 29 , 30 ) . Of particular interest are the findings of Claustre et al ( 31 ) that enzymic hydrolysates of casein induced a strong mucin secretion in rat jejunum and this was attributed to the presence of an opioid peptide, β-casomorphin-7.…”
Section: Discussionmentioning
confidence: 99%
“…Findings on the effect of ethanol on gastric acid secretion are controversial. While some studies prove that ethanol has a mild stimulatory effect on gastric acid secretion in concentrations below 5% and no or a slight inhibitory effect in concentrations above 5%, , others found ethanol to be a potent stimulant. , …”
Section: Introductionmentioning
confidence: 99%